THE PRESIDENT'S POLITICAL POLICY ABDURRAHMAN WAHID ABOUT INDONESIAN MILITARY YEARS 1999-2001 - Adam Sukarno Putra; Nurul Umamah; Sumarno Sumarno (History Education, University of Jember, 2019)
Abdurrahman Wahid is the fourth president of the Republic of Indonesia. During the leadership of President Abdurrahman Wahid has big problems to be resolved soon, namely in relation to the demands of reforms in which there is a demand to liberate the power of civilian control over the military by removing the concept of dual function of ABRI. The problem formulation in this research is, (1) What is behind the emergence of Abdurrahman Wahid's political policy on the Indonesian Military, (2) What is Abdurrahman Wahid's political policy on the Indonesian Military?, and (3) What are the implications of Abdurrahman Wahid's political policy on the Indonesian Military. This study uses William N Dunn's public policy approach and military civil-relations theory. The result of this research is the demands of reform which become the background of political policy of President Abdurrahman about the Indonesian military. The political policy is to abolish the concept of dual function of ABRI, separation of TNI and Polri, and to increase Indonesian military budget Keywords: Gus Dur, Political Policy, Indonesian Military